Assembly of High Molecular Weight Kininogen and Activation of Prekallikrein on Cell Matrix - Motta, G.; Shariat-Madar, Z.; Mahdi, F.; Sampaio, C. A. M.; Schmaier, A. H. (Thrombosis and Haemostasis, 2001)
Investigations determined if extracellular matrix of endothelial cells (EC) is a platform for HK assembly and PK activation. In buffers containing bovine serum albumin, biotin-HK binding to ECV304 cells or their matrix requires ≥ 50 µM added Zn 2+. Ortho-phenanthroline or a HK domain 5 peptide blocks HK binding. Binding to umbilical vein EC or matrix, but not ECV304 cells or matrix, is mediated by cytokeratin 1. Biotin-HK binds to ECV304 cells or matrix with a Kd of 15.8 or 9.0 nM and a Bmax of 2.6 107 or 2.4 107 sites/cell, respectively. PK activation on ECV304 cells or matrix is blocked by antipain or SBTI and corn trypsin inhibitor partially inhibits kallikrein formation. PK activation occurs on ECV304 cells or matrix prepared without serum or in human factor XII deficient serum, indicating that the PK activator is not factor XIIa. EC matrix promotes plasminogen activation after the assembly of HK, PK and pro-urokinase. These studies indicate that matrix of various EC has the ability to assemble HK allowing for PK activation and subsequent activities.Abbreviations: EC: endothelial cells, FXII: factor XII, HK: high molecular weight kininogen, HKa: bradykinin-free HK, PK: plasma prekallikrein, Pro-UK: pro-urokinase, uPAR: urokinase plasminogen activator receptor, tcuPA: twochain urokinase, CK1: cytokeratin 1, SBTI: soybean trypsin inhibitor, HUVEC: human umbilical vein endothelial cell, SDS-PAGE: sodium dodecyl sulfatepolyacrylamide gel electrophoresis, CTI: corn trypsin inhibitor, p-APMSF: p-amidinophenylmethylsulfonylfluoride, EBSS: Earle’s Balanced Salt Solution
Keywords: HMW kininogen; prekallikrein; endothelial cells; extracellular matrix; pro-urokinase; plasminogen